2008
DOI: 10.1002/jor.20623
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of major lineage‐defining factors in human bone marrow cells: Effect of aging, gender, and age‐related disorders

Abstract: Adult bone marrow cells (BMCs) include two populations:;mesenchymal stem cells (MSCs), which can differentiate into bone, cartilage, and fat; and hematopoietic stem cells (HSCs), which produce all mature blood lineage. To study the effect of aging, gender, and agerelated disorders on lineage differentiation, we performed quantitative RT-PCR to examine mRNA expression of the major factors defining BMC lineage, cbfa1 for osteoblasts, ppar-gamma for adipocytes, sox9 for chondrocytes, and rankl for osteoclasts, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 64 publications
1
61
4
Order By: Relevance
“…Our study was limited by the fact that the specimens were harvested from patients with osteoarthritis of the hip or femoral neck fracture during prosthetic replacement surgery of the hip joint, so these diseases may have influenced the results. Moreover, the age and sex of the patients, physique, and bone density were not constant, and there may have been individual differences in their response (6,29). However, these issues do not cause us to doubt that factors related to bone metabolism are secreted by bone marrow adipocytes, and that these may have a significant effect on the body.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was limited by the fact that the specimens were harvested from patients with osteoarthritis of the hip or femoral neck fracture during prosthetic replacement surgery of the hip joint, so these diseases may have influenced the results. Moreover, the age and sex of the patients, physique, and bone density were not constant, and there may have been individual differences in their response (6,29). However, these issues do not cause us to doubt that factors related to bone metabolism are secreted by bone marrow adipocytes, and that these may have a significant effect on the body.…”
Section: Discussionmentioning
confidence: 99%
“…Histomorphometric studies indicate that the age-related decrease in bone mass in mice is associated with increased osteoblastic and osteocytic apoptosis that may be caused by enhanced oxidative stress with age (Almeida et al, 2007). In one human study, no age-related changes in gene expression level of Bcl-2 (a marker for apoptosis) were detected in MSC obtained from 80 healthy subjects (Jiang et al, 2008), but in a recent study, Zhou et al (2008) reported a age-related increase in the number of apoptotic cells in MSC cultures. These discrepancies may be related to the sensitivity of the method employed.…”
Section: Age-related Decline In the Functional Lifespan Of Osteoblastsmentioning
confidence: 99%
“…Meanwhile, expression of peroxisome proliferator active receptor gamma (PPARG), an adipogenic transcription factor, increased nearly fourfold and SRY (sex determining region Y)-box 9(SOX9, the master regulator of chondrogenesis) was unchanged. 37 Kasper et al studied the changes in SD rat BMSC proteomes associated with aging, and attributed the inverse correlation between age and replicative potential in part to a decline in cellular responsiveness to mechanical stimuli resulting from a less dynamic actin cytoskeleton. 38 Veronesi and coworkers reviewed studies on aging's effects on ADSCs and BMSCs, and concluded that, although some authors found no differences in the proliferative capacity of MSCs, the majority of studies agreed that decreases in MSC proliferation rate and osteogenic capacity were observed with age.…”
Section: Donor Age Dependent Cell Senescencementioning
confidence: 99%